EFFECTIVENESS OF THE NEW SEED TREATMENT PREPARATION VIBRANCE INTEGRAL AGAINST DISEASES AND PESTS ON SPRING BARLEY - Kosylovych, Г.; Holiachuk , Ю. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
Pre-sowing treatment of seed is an important link in the production of plant products, a significant reserve for increasing plant productivity and improving crop quality. Pre-sowing treatment of seed material aims to protect plants from diseases caused by infected seeds or soil, as well as to protect seedlings and plant seedlings from soil pests. It is of primary importance in the modern systems of protecting spring barley plants from harmful organisms. For the treatment of spring barley seeds before sowing against diseases and pests, it is suggested to apply fungicide-insecticide Vibrance Integral, 235 FS ((sedaxane, 25 g/l + fludioxonil, 25 g/l + tebuconazole, 10 g/l + thiamethoxam, 175 g/l) in the rate 2 l/t. The use of Vibrance Integral, 235 FS for pre-sowing treatment of spring barley seeds was an effective measure to prevent damage to plants by pathogens of a complex of root and stem rots (Fusarium, Cochliobolus sativus), species of bunt (Ustilago nuda, Ustilago hordei), net (Pyrenophora teres) and striped (Pyrenophora graminea) leaf spots, as well as to limit damage to plant seedlings by soil pests (Agriotes), flea beetles (Phyllotreta vittula, Chaetocnema hortensis), cereal leaf beetles (Oulema melanopus, Oulema lichenis), cereal flies (Mayetiola destructor, Oscinella pusilla) and cereal aphids (Sitobion avenae, Brachycolus noxius). The results of the present studies confirm its high fungicidal activity against seed and soil infection, as well as its high insecticidal efficiency against soil and seedling pests. The pre-sowing treatment of spring barley seeds with Vibrance Integral, 235 FS pesticide in the rate 2 l/t did not have a negative effect on seed quality, on the contrary, the drug provided 1.7–1.9% better indicators of germination energy and laboratory germination than the control. Using the fungicide-insecticide Vibrance Integral, 235 FS to pre-sowing treatment of spring barley resulted in a higher yield, i.e. a significant additional grain yield as compared to the control was 13.4 t/ha.